2014
DOI: 10.1530/eje-14-0076
|View full text |Cite
|
Sign up to set email alerts
|

Small medullary thyroid carcinoma: post-operative calcitonin rather than tumour size predicts disease persistence and progression

Abstract: Objective: Recently, small medullary thyroid carcinomas (smallMTCs; %1.5 cm) are frequently diagnosed, occasionally as incidental findings in surgical specimens. Their clinical course varies. We examined tumour size as a predictor of clinical behaviour. Design: A retrospective study. Methods: A total of 128 smallMTC patients (35.2% males and 45% familial) were followed up for 0.9-30.9 years. According to tumour size (cm), patients were classified into four groups: group 1, 0.1-0.5 (nZ33); group 2, 0.6-0.8 (nZ3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…MTC survival could have been affected by several prognostic factors such as age, 21 male gender, invasive histological characteristics, 22 the adequacy of primary surgery 2,23 and the calcitonin doubling time. 2,24,25 In agreement with other studies, we found that male gender, tumour size >2 cm and distant metastasis were significant prognostic factors for survival. In the present study, although there was a decrease in tumour size, the percentage of male and distant metastasis remained similar over time, and the proportion of tumour >2 cm remained about 25% even in 2011-2012.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…MTC survival could have been affected by several prognostic factors such as age, 21 male gender, invasive histological characteristics, 22 the adequacy of primary surgery 2,23 and the calcitonin doubling time. 2,24,25 In agreement with other studies, we found that male gender, tumour size >2 cm and distant metastasis were significant prognostic factors for survival. In the present study, although there was a decrease in tumour size, the percentage of male and distant metastasis remained similar over time, and the proportion of tumour >2 cm remained about 25% even in 2011-2012.…”
Section: Discussionsupporting
confidence: 92%
“…Although pathologic characteristics and recurrence‐free survival improved during recent periods, mortality was unchanged over time. MTC survival could have been affected by several prognostic factors such as age, male gender, invasive histological characteristics, the adequacy of primary surgery and the calcitonin doubling time . In agreement with other studies, we found that male gender, tumour size >2 cm and distant metastasis were significant prognostic factors for survival.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, patients’ probability for cure from MTC has been found to be associated with lymph node status, ranging from 95% when no lymph nodes are involved, 31–57% when 1–10 lymph nodes are involved, and 0–4% when more than 10 lymph nodes are involved with MTC [12-14]. Previous publications have demonstrated the possibility of lymph node involvement regardless of the size of the tumor and even in micro-medullary carcinomas of less than 0.5 cm in diameter [15]. The performance of thyroidectomy prior to the development of MTC and definitely prior to the development of lymph node involvement in nearly all cases is a crucial aspect of the prophylactic nature of the procedure.…”
Section: Discussionmentioning
confidence: 99%